Antioxidant and Antibacterial Activities of Crude Extracts of Homalium paniculiforum Stem - Liu, Pinghuai; Xu, Qiongqing; Wang, Chunniu; Chen, Deli; Sun, Yuwan (Asian Journal of Chemistry, 2013)
The present study reports antioxidant and antibacterial activities of crude extracts of Homalium paniculiforum stem using high-throughput assay. The crude extracts were prepared in two methods, accelerated solvent extraction and conventional solvent extraction, successively using petroleum ether, ethyl acetate, n-butanol and water. The EC50 values were calculated for DPPH and FRAP value in order to evaluate the antioxidant efficiency of all of the extracts. The MIC values were judged by visual for resazurin microtitre assay in order to evaluate the antibacterial ability of all of the extracts. In comparison, accelerated solvent extraction method can improve antioxidant and antibacterial ability of the extracts more or less. The conventional solvent n-butanol extract (EC50 = 47.99 mg/L, FRAP value = 434.8 ± 51.3 mol TE/g) exhibited highly striking 2, 2-diphenyl-1-picrylhydrazyl radical-scavenging activity, ability of chelating ferrous ions. The conventional solvent petroleum ether extract (EC50 > 200 mg/L, FRAP value = 26.6 ± 7.3 mol TE/g ) exhibited the lowest. Resazurin microtitre assay show that the conventional solvent extract ethyl acetate and petroleum ether is more suitable for further study on chemical constituents with antimicrobial activity because of simply preparation and inhibition to all the strains.